Innovative Diagnostic and Therapeutic Methods in Clinical Medicine: A Systematic Review - Pavlyshyn, Ivanna; Bundz, Andriana (Futurity Medicine, 2026)
Aims: Clinical medicine has evolved rapidly since the COVID-19 pandemic owing to accelerated development of innovative diagnostic and therapeutic technologies. Despite substantial progress, most existing studies focus on isolated technologies rather than integrated systems. This systematic review aimed to synthesise recent evidence on emerging innovations in diagnosis and treatment, assess their clinical effectiveness and safety, and identify implementation barriers affecting real-world adoption. Study design: Systematic review conducted in accordance with PRISMA 2020 guidelines. Methodology: Five major databases (PubMed, Scopus, Web of Science, Google Scholar, and the Cochrane Library) were searched for studies published between January 2020 and December 2025. Eligible publications included randomised controlled trials, cohort studies, diagnostic accuracy studies, systematic reviews, and implementation research evaluating innovative diagnostic or therapeutic approaches in clinical settings. Preclinical studies, small case series, commentaries, and paediatric-only studies were excluded. Two reviewers independently screened 4,580 titles and abstracts and assessed 210 full-text articles, resulting in 29 included studies. Data extraction encompassed study design, population characteristics, innovation type, clinical outcomes, and implementation factors. Results: The included studies addressed AI-based diagnostic systems, molecular and immunotherapies, digital health tools, imaging techniques, CRISPR-based diagnostics, vaccines, and therapeutic management strategies. Vaccines and antibody-based interventions demonstrated highest effectiveness, followed by clinical therapies and telemedicine applications. AI-based diagnostic tools performed comparably to non-expert clinicians but remained inferior to specialist assessment. Digital health interventions improved outcomes in heart failure and diabetes management, while molecular and immunotherapies yielded inconsistent results. Implementation barriers included high costs, infrastructural constraints, limited digital literacy, and regulatory challenges. Conclusion: Emerging innovations have enhanced diagnostic accuracy, treatment efficacy, and patient monitoring across clinical domains. Nevertheless, methodological heterogeneity and technology adoption limitations moderated overall effectiveness. These findings highlight the need for adaptive trial designs, implementation research, and equity-oriented deployment strategies to enable scalable integration of emerging technologies into routine clinical practice.